Design and Development of Corporate Gamification in Training Framework for Sustained Engagement in Malaysian Customer Service Industries. - Ben, Tan Chee (2019)
The purpose of this research was to propose a guideline under a gamification framework for corporate training that would help instructional designers or corporate trainers to improve instructional designs through a systematic approach when gamifying a training programme. The traditional methods used in corporate sector training were not engaging and interactive, as well as ineffective. Hence, gamification methods are used in the corporate world to improve training. Effective gamification could bring in savings and profit returns, resulting in the use of gamification in many businesses. However, there were no clear guidelines for effective gamification design. This study investigated the usage of a design-based research (DBR) approach on gamification in corporate training.This research used a mixed method research design for data collection and analysis. For the training design in this research, the DBR approach was used to ensure the successful implementation of a gamification framework for corporate training. Methodological triangulation was conducted to enhance reliability and validity through cross-checking data from multiple sources such as interviews, surveys and observations. Authorisation from the corporate company researched was obtained to avoid any ethical breach. The training was implemented in a real-world setting, hence, the data gathered was based on a real training implementation. A total of 702 participants from the corporate sector were involved in the training. There were eight trainers or practitioners of this programme and they were evaluated by a classroom auditor or observer. Three pilot classes were conducted with 62 participants. The remaining 640 participants were divided into 31 classes.The Gamification Training Solutions Framework (GTSF) was a guideline proposed for instructional designers to include games as an important factor in designing instruction. Based on this study, 98% of 640 participants agreed that the overall course was effective. Feedback from participants showed that 97% agreed that the GTSF used had effective course content and design. Ninety-seven percent (97%) of the 640 participants recommended the course to others. In conclusion, future corporate training could use the GTSF as a quick guideline for instructional designers to implement training using gamification.